Catalunya i la Guerra de Successió d’Espanya : (1702-1714) - Alcoberro, Agusti (Acta Hispanica, 2014)
The War of the Spanish Succession affected the entire continent of Europe directly or indirectly. Within the Spanish Monarchy, Catalonia and the other states of the Crown of Aragon sided with Archduke Charles of Austria (Charles III), while Crown of Castile lent its support to Duke Philip of Anjou (Philip V). After the Peace of Utrecht, Catalonia prolonged its resistance for 14 more months under a republican government. At the end of the war, the victors imposed repression, exile and the end to the Catalan constitucions.